(untitled) (Revista Argentina de Musicología, 2023)
This paper is based on field research carried out in Buenos Aires in which we delve into the processes of signification and representation of the elements that have reified the Galician musical reality in this city. The dichotomy opened in the last quarter of the 20th century between the categories of "traditional music" and "celtic music" has developed to a point where it is difficult to define their limits. Likewise, globalization, communication, and exchange between actors and institutions have profoundly transformed the musical and extra-musical elements associated with Galicianness into a music that is deterritorialized and strongly defined by generational succession, which provokes a profound disconnection with its place of origin. The identity perspectives within the Galician community are analyzed from a sociological prism in which the performative elements, the music market, industry, the material mediations, agency, and symbolic constructions that revolve around it play a fundamental role. These elements will define the elaboration of a narrative capable of encompassing the heterogeneity of the musical experience of the Galician and Porteño actors who participate directly or indirectly in shaping this complex and lively cultural and social reality.